2018
DOI: 10.1126/science.aas8694
|View full text |Cite
|
Sign up to set email alerts
|

A landscape of disgust

Abstract: Parasite avoidance behavior affects ecology and evolution in ways similar to predator avoidance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
128
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(153 citation statements)
references
References 16 publications
3
128
1
2
Order By: Relevance
“…In nature all organisms under constant threat of attack by pathogens and parasites (microparasites, (including bacteria and viruses) and macroparasites (eg, helminths, arthropods [biting insects]) in what has been referred to as a “landscape of disgust” . Individuals harbor a range of parasites as well as both beneficial and potentially pathogenic bacterial and viral components.…”
Section: Social Cognition Disgust and Pathogen Avoidancementioning
confidence: 99%
See 2 more Smart Citations
“…In nature all organisms under constant threat of attack by pathogens and parasites (microparasites, (including bacteria and viruses) and macroparasites (eg, helminths, arthropods [biting insects]) in what has been referred to as a “landscape of disgust” . Individuals harbor a range of parasites as well as both beneficial and potentially pathogenic bacterial and viral components.…”
Section: Social Cognition Disgust and Pathogen Avoidancementioning
confidence: 99%
“…Although the majority of investigations of the effects infection on social and mate responses have been carried out under laboratory conditions there is evidence that the findings are consistent with the results from natural and semi‐natural conditions . Indeed it has been suggested that in nature animals the landscape of disgust from pathogen and parasite threat that has far reaching implications for population dynamics and overall behavior . Under natural conditions odor and other sensory cues (eg, ultrasonic vocalizations), may result in female mice being more likely to detect and locate healthy males resulting in the disgust associated avoidance of a less preferred male and biased mating.…”
Section: Odors Mate Choice and Pathogen Avoidancementioning
confidence: 99%
See 1 more Smart Citation
“…To avoid costly effects of parasitism, hosts can mount a range of general defense strategies broadly including avoidance, resistance, and tolerance (Råberg, Graham, & Read, ). Owing to the high cumulative fitness costs of parasitism, there is strong selection for parasite avoidance—relying on indirect cues driven by long‐term associations—to minimize infection risk (Weinstein, Buck, & Young, ). Resistance and tolerance are host traits that have evolved to alleviate the health and fitness effects of parasitism.…”
Section: Introductionmentioning
confidence: 99%
“…cumulative fitness costs of parasitism, there is strong selection for parasite avoidance-relying on indirect cues driven by long-term associations-to minimize infection risk (Weinstein, Buck, & Young, 2018). Resistance and tolerance are host traits that have evolved to alleviate the health and fitness effects of parasitism.…”
mentioning
confidence: 99%